Neurotechnology Applied to Medicine. Analysis of Patients Undergoing Neuro Endoscopy in Triventricular Obstructive Hydrocephalus - Gonzalez-Argote, Javier (Universitas Pendidikan Indonesia (UPI), 2023)
Hydrocephalus is the condition that has benefited the most from neuroendoscopy and is largely responsible for its emergence. The purpose of this study was to evaluate the application of endoscopic third ventriculostomy to treat obstructive triventricular hydrocephalus in the Neurosurgery Department. A descriptive study was conducted in a hospital in the Buenos Aires suburbs involving patients admitted to the neurosurgery department diagnosed with obstructive triventricular hydrocephalus. We reviewed 37 male patients (75.5 %) and 12 female patients (24.5 %). Hydrocephalus grade II was observed in 87.7%, and only 16.3% were associated with transependymal flow and hydrocephalus grade III. These imaging signs allowed us to diagnose the type of obstructive triventricular hydrocephalus, as well as to have an initial reference for postoperative evaluation and follow-up of diagnosed patients, relying on the dimensions of the third ventricle, Evans index, and Morlan scale for hydrocephalus grade, enabling quantification of these signs during their progression.